The Analysis of Students’ Affective Through Learning with Problem Posing Approach - Azhil, Imam Muhtadi; Lutfianto, Moch.; Ernawati, Agustin (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
Affective need to be considered by the teacher because it makes learning more effective. Therefore, the aim of this research is to analyse students’ affective through learning with problem posing approach. The present research employs qualitative study. The subject of the research involved 39 students of science class 3 on grade X of Wachid Hasyim 2 Senior High School in Taman, Sidoarjo. The instruments to analyse students’ affective consists of observation note, questionnaires and interview guide. The data is analysed throughout descriptive qualitative. Implementation of the research emphasised composing and problem posing aspects which was done by the students on linear equation system of three variables. The result of the analysis shows that the students’ affective could be identified through receiving, responding, valuing, organizing and characterizing by a value. The subjects with high affective had completely met the aspects of affective and tended to likely be more active during the learning process.